Evaluation of internal markers as determinants of fecal dry matter output and digestibility in feedlot sheep - Cabral, Ícaro dos Santos (2017)
This study aimed to evaluate the fecal recovery of the internal markers indigestible dry matter (iDM), indigestible neutral detergent fiber (iNDF), and indigestible acid detergent fiber (iADF) and to compare them as estimators of the fecal dry matter output (FDMO) and digestibility of the dry matter (DM) with values observed in total feces collection in trials with feedlot sheep. For this, 82 sampling units from two experiments were evaluated. Internal markers were quantified in the feed supplied, orts, and feces. The recovery of the markers was determined by the comparison of the amount of marker consumed and excreted. Fecal dry matter output and digestibility were determined based on the amount of marker consumed and on its concentration in the feces through individual collections directly from the rectum of the animals, with values compared with those observed in the total feces collection from orthogonal contrasts. The mean bias, the concordance correlation coefficient, and the mean squared prediction error were also evaluated. For all statistical procedures, the critical level of probability for type-I error was fixed at 0.05. The marker iDM showed complete fecal recovery (100.03%) and was efficient in estimating FDMO (482.9 g day-1) and DM digestibility (542 g kg-1) as compared with the values observed in the total feces collection (454.7 g day-1 and 561 g kg-1 for FDMO and DM digestibility, respectively). The iNDF and iADF markers did not show complete recovery in the feces and were not effective in the estimate of FDMO and DM digestibility.